Species diversity, living above and below ground biomass, and carbon stock assessments of Mangrove forest in Tandog Island Station 2, Taklong Island National Marine Reserve, Nueva Valencia, Guimaras - De Los Santos, Kingsley John
Mangroves are halophytic plants that are known as primary produces in coastal ecosystems and have a key role in total carbon cycle due to their high carbon stock capacity relative to other ecosystems. This vast potential makes the mangroves a major carbon sink and source. Tandog Group of Islands are protected islands which are part of the Taklong Island National Marine Reserve (TINMR). The area has an extensive mangrove cover and has very minimal anthropogenic disturbances which can serve as baseline for comparison for other mangrove studies which concerns on species diversity, above and below ground biomass and carbon sequestered. This study specifically aims to (a) determine the area and map out the selected mangrove patches, (b) assess the species composition and community structure at each sampling site, (c) determine above and below ground biomass and carbon stock of live vegetation, and (d) convert the total carbon density into carbon dioxide equivalents. However, one limitation of this study is that the biomass accounted is only on the living vegetation of the forest using published allometric equations. The marine protected area has 14 species of mangroves however only 3 were present in the plots. The average stand basal area (SBA) was 16.20m2 ha-1 which implies the maturity of the forest. It was also found that the forest has a high tree and wildling density which is a good indicator of an ideal community structure with good regeneration potential. The Shannon-Weiner Index showed very low diversity although it is worth noting that mangrove ecosystems often score low in diversity indices. The total area of the site is 4.09 ha with a total C stock of 886.1mg which can be translated to 1,504.6mg of CO2 potential. These values show the great potential of mangroves as carbon sinks that further reinforces the results of other studies about the capacity of mangroves in climate change mitigation.